2018
DOI: 10.1080/02786826.2018.1488078
|View full text |Cite
|
Sign up to set email alerts
|

Generation of high concentrations of respirable solid-phase aerosols from viscous fluids

Abstract: High outputs of respirable solid-phase aerosols were generated from viscous solutions or suspensions of low and high molecular weight polyvinylprrolidone (PVP) solutions, 10% (w/v) albumin and, gamma-globulin solutions as well as 10.3% (w/v) surfactant suspensions. A central fluid flow was aerosolized by coaxial converging compressed air. The water was evaporated from the droplets using warm dilution air and infrared radiation. The resulting aerosol particles were concentrated using a virtual impactor. The aer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
(51 reference statements)
1
1
0
Order By: Relevance
“…Therefore, the separation of viscous ink into droplets was hindered. Similar results were obtained by Heng et al [44] who generated solid phase aerosols from viscous solutions or suspensions and found that the increase in velocity in the range from 4 cSt to 39 cSt caused a modest increase in the median aerodynamic diameter. On the other hand, low viscosities usually lead to satellite formation.…”
Section: Resultssupporting
confidence: 89%
“…Therefore, the separation of viscous ink into droplets was hindered. Similar results were obtained by Heng et al [44] who generated solid phase aerosols from viscous solutions or suspensions and found that the increase in velocity in the range from 4 cSt to 39 cSt caused a modest increase in the median aerodynamic diameter. On the other hand, low viscosities usually lead to satellite formation.…”
Section: Resultssupporting
confidence: 89%
“…The average concentration in the chamber measured during the exposure period of the test substance was < 20%, which satisfies the conditions for aerosol generation in OECD TG412 17 . This was thought to be due to the increase in compressed air pressure to increase the concentration of the test substance in the chamber when the test substance was generated 18 .…”
Section: Discussionmentioning
confidence: 99%